2011
DOI: 10.1186/1475-2867-11-38
|View full text |Cite
|
Sign up to set email alerts
|

The chemopreventive effect of Ginkgo biloba and Silybum marianum extracts on hepatocarcinogenesis in rats

Abstract: Background/objectiveThis study was designed to evaluate the potential chemopreventive activities of Ginkgo biloba extract (EGb) and Silybum marianum extract (silymarin) against hepatocarcinogenesis induced by N-nitrosodiethylamine (NDEA) in rats.MethodsRats were divided into 6 groups. Group 1 served as normal control rats. Group 2 animals were intragastrically administrated NDEA at a dose of 10 mg/kg five times a week for 12 weeks to induce hepatocellular carcinoma (HCC). Groups 3 and 4 animals were pretreated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 58 publications
3
35
0
Order By: Relevance
“…Investigations show that SME exhibits excellent hepatoprotective property by restoring the hepatic marker enzymes and antioxidant property reversing the oxidant--antioxidant imbalance during CCL4, diethyl nitrosamine or methotrexate-induced oxidative stress in rats [Mao et al, 2012;El Mesallamy et al, 2011;Ghaffari et al, 2011]. Silymarin reduced high fructose diet-mediated increase in plasma pro-infl ammatory cytokines, C-reactive protein (CRP), interleukin-6 (IL-6), interferon-gamma (IFN-γ) and tumor necrosis factor (TNF) levels [Prakash et al, 2014].…”
Section: Effect Of Sme On Hfd-induced Hepatopathymentioning
confidence: 99%
“…Investigations show that SME exhibits excellent hepatoprotective property by restoring the hepatic marker enzymes and antioxidant property reversing the oxidant--antioxidant imbalance during CCL4, diethyl nitrosamine or methotrexate-induced oxidative stress in rats [Mao et al, 2012;El Mesallamy et al, 2011;Ghaffari et al, 2011]. Silymarin reduced high fructose diet-mediated increase in plasma pro-infl ammatory cytokines, C-reactive protein (CRP), interleukin-6 (IL-6), interferon-gamma (IFN-γ) and tumor necrosis factor (TNF) levels [Prakash et al, 2014].…”
Section: Effect Of Sme On Hfd-induced Hepatopathymentioning
confidence: 99%
“…In addition, SIL treatment exhibited significant hepatoprotection against CCl4-induced hepatotoxicity in the rats, by lowering the elevated serum activity of ALT, AST and ALP induced by the toxin (Salam et al, 2009;El-Maddawy and Gad, 2012). Moreover, extracts from Silybum marianum beneficially downregulated the increases in serum ALT, AST and GT activities induced by the carcinogen NDEA (El Mesallamy et al, 2011). In clinical studies, therapy with SIL in patients with various patterns of liver diseases beneficially modulated the activities of transaminases and levels of total bilirubin in the serum (Feher et al, 1989;Dixit et al, 2007;Hajiani, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, extracts obtained from SIL can be used in chemoprevention against hepatocarcinogenesis caused by hepatitis C virus or chemicals (Mastron et al, 2015). In rats, for example, it protected the hepatocytes against hepatocarcinogenesis induced by Nnitrosodiethylamine (NDEA), as it ameliorated the hepatic markers of oxidative stress (LPO and antioxidants such as GSH, SOD and GPx) induced by this carcinogen (El Mesallamy et al, 2011). In view of above, SIL, due to its ability to protect against FLU hepatotoxicity in addition to its anti-carcinogenic activity, appeared to be a promising complementary therapeutic drug which may act in synergistic fashion with FLU in the treatment of prostatic carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…It was clearly demonstrated that silymarin exerts a strong protective effect against oxidative stress damage at the protein level which has a direct connection to its use as hepatoprotector for chronic inflammatory liver diseases and liver cirrhosis (Herman et al 2011). Alongside with its antioxidant properties and its role in stimulating protein synthesis and cell regeneration (Tawaha et al 2007), silymarin may also reduce incidence of certain forms of cancer (Al Mesallamy et al 2011). Silymarin was proved to protect liver and kidney cells from toxic effects of drugs including chemotherapy and radiotherapy (Meghreji Moin et al 2010 andPrabhaba et al 2010).…”
mentioning
confidence: 99%